2021
DOI: 10.1002/joc.7301
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes in global dryland temperature and precipitation

Abstract: Changes in dryland temperature and precipitation are essential components of dryland climate change. This study applies the use of the monthly reanalysis data product of ERA5, which has a spatial resolution of 0.25 , to investigate the changes in the dryland climate between 1979 and 2018. The result revealed warming and drying of the drylands in recent decades, most notably in the current decade. The general global dryland temperature and precipitation increased and decreased significantly (0.01 significance l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…The data are from 1950 to the present with a spatial resolution of 0.25° in latitude and longitude (Hersbach et al., 2020). The reanalysis procedure integrated instrumentation observations as well as available satellite data (Calì Quaglia et al., 2021; Daramola & Xu, 2022; Fan et al., 2022; Gleixner et al., 2020; Jiang et al., 2021). Monthly averaged surface air temperature and total precipitation from the data set are used in identifying climate types (Table 1) for our study period from 1960 to 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The data are from 1950 to the present with a spatial resolution of 0.25° in latitude and longitude (Hersbach et al., 2020). The reanalysis procedure integrated instrumentation observations as well as available satellite data (Calì Quaglia et al., 2021; Daramola & Xu, 2022; Fan et al., 2022; Gleixner et al., 2020; Jiang et al., 2021). Monthly averaged surface air temperature and total precipitation from the data set are used in identifying climate types (Table 1) for our study period from 1960 to 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Reanalysis datasets show that the global semi-arid and arid regions show a significant warming and drying trend, but there are obvious regional differences in precipitation changes [6]. Specifically, precipitation in southern Asia, southern Africa, and the northeastern part of the drylands of North America have increased significantly, while precipitation in central North America, southwestern South America, eastern Africa and western Asia have decreased significantly [7][8][9]. Based on the above research, we found that the research on climate change in arid regions is mainly focused on large-scale areas, but there is less attention to climate change in different ecological systems and different altitude gradients in arid regions.…”
Section: Introductionmentioning
confidence: 99%
“…A recent assessment of climatic trends across the world's drylands between 1979 and 2018 revealed a general increase in temperatures and decrease in precipitations, with the most notable changes recorded during the last decade. During this entire period, the rate of temperature increase has been 0.032 °C yr −1 , and the rate of precipitation decrease has been 0.074 mm month −1 yr −1 (Daramola and Xu, 2022). Yet, at the regional scale, variations are more dramatic.…”
Section: Desertificationmentioning
confidence: 93%